3-(3-Methylphenyl)-2-thioxo-1,3-thiazolidin-4-one - Shahwar, Durre (International Union of Crystallography, 2009)
In the title compound, C(10)H(9)NOS(2), the dihedral angle between the rhodanine (2-thioxo-1,3-thiazolidin-4-one) and 3-methylphenyl rings is 83.30 (3)°. The H atoms of the methyl group are disordered over two set of sites with an occupancy ratio of 0.58 (3):0.42 (3). In the crystal, the molecules interact by way of C—H⋯π and C=O⋯π interactions.